Insiders, outsiders and the politics of corporate governance: How ownership shapes party positions in Britain, Germany and France - Helen Callaghan (Max Planck Institute for the Study of Societies, 2007)
This paper argues that differences in the dispersion of corporate ownership can help explain why party positions on corporate governance vary across countries and over time. Expectations that left/right conflicts should pitch capital against labor overlook that "capital" is not a homogenous constituency with regard to corporate governance issues. Two segments of capital with diverging interests need to be distinguished: "insiders" with voice over company management, and "outsiders" who exercise arms-length control by threatening exit. Party positions depend on the relative size of the insider and outsider constituencies, which in turn depends on countries' prevailing structure of corporate ownership. The paper draws on evidence from British, German and French political debates over takeover regulation from the 1950s onward. It speaks to the literatures on party competition, corporate governance, Varieties of Capitalism and institutional change.
Keywords: 300; Parteipolitik; Corporate Governance; Eigentümerstruktur; Öffentliche Meinung; Übernahme; Konzernrecht; Großbritannien; Deutschland; Frankreich